In the Water with White Sharks (Carcharodon carcharias): Participants' Beliefs toward Cage-diving in Australia. (3rd May 2016) - Apps, Kirin; Dimmock, Kay; Lloyd, David; Huveneers, Charlie
ABSTRACT: White shark ( Carcharodon carcharias ) cage-diving tourism is a controversial activity that provokes emotional and often opposing points of view. With increasing demand for shark tourism since the 1990s, the un- derlying determinants driving this growth in participation remain unclear. This paper adopts a qualitative approach to investigate beliefs underlying tourists' choice to observe white sharks while cage-diving at the Neptune Islands, South Australia. Elicitation surveys gathered responses from a sample ( n = 86) of cage-diving participants. Content analysis of the responses revealed the decision to cage-dive with white sharks is driven by factors including education and the perceived naturalness of the experience. The findings of this study indicate an opportunity for cage-dive operators to pro- vide in situ education and interpretation with potential for increased tourist satisfaction and shark conservation outcomes.